Influence of foreign policy in Turkey's role as a transit gas hub country in eastern mediterranean natural gas bonanza - Akman, Yasemin (İstanbul Bilgi Üniversitesi, 2020)
ABSTRACT: Widely known as the Ibn Khaldun says that geography is destiny, in our modern world, I believe that geography of a country would only be a denominator, yet the foreign policy absolutely is the numerator of the equation. Moreover, I believe that the geography of a country gains meaning with the power of its foreign policy. To that end, this paper aims to research the influence of the foreign policy of Turkey for its aim on being an energy hub, in more micro view, for to be a transit natural gas hub. As an energy import dependent country, Turkey is predominantly shaping its foreign policy according to her energy policies. On the other hand, Turkey's strategic position in the world, from geopolitical perspective, have induced Turkey to experience versatile foreign policy. The first chapter of this paper gives brief information for the subject. The second chapter includes the basic definitions and findings of the Eastern Mediterranean natural gas deposit. The second chapter also includes my research question and the methodology of this thesis. The methodology is based on the literature review. The third chapter is about the foreign policy of Turkey from 2010 to 2018 towards the countries concerned and key findings of the foreign policies. Conclusion includes the outcomes and responds the research question.

ÖZET: Ibn-I Haldun'un coğrafya kaderdir söylemine yönelik inancım bu denklemde payın dış politika, coğrafyanın ise paydası olduğu yönündedir. Bir ülkenin coğrafyasının geliştirdiği dış politika ile anlam kazandığına inanmaktayım. Buna göre, bu tez Türkiye'nin Doğu Akdeniz doğal gaz enerji havzası ile enerji merkezi ülke olma idealindeki ve hatta daha mikro olarak bir doğal gaz merkez geçiş ülkesi olma yolunda dış politikanın etkisini araştırmıştır. Doğal gaz ithalatçısı bir ülke olarak Türkiye dış politikasını belirleyen ana unsurların başında enerji politikaları gelmektedir. Öte yandan, Türkiye'nin dünyadaki benzersiz konumu, jeopolitik açıdan Türkiye'yi dinamik dış politikalar deneyimlemesine neden olmuştur Tezin birinci bölümü konu hakkında özet bilgi vermektedir. Tezin ikinci bölümünde ise terimsel bağlamda tanımlamalar yapılmıştır. Bununla birlikte araştırma sorusu ve yöntem de tezin ikinci bölümünde bulunmaktadır. Tezin üçüncü bölümünde, ilgili ülkeler ile Türkiye'nin 2010 – 2018 yılları arasında geliştirmiş olduğu dış politika incelenmiştir ve sonuçlar bulgular kısmında açıklanmıştır. Tezin sonuç kısmında, erişilen bulgular eşliğinde araştırma sorusuna cevap verilmiş ve neticeler belirtilmiştir.
Doğu Akdeniz doğalgaz yatağında Türkiye'nin merkez gaz geçiş ülkesi rolüne dış politikanın etkisi
Keywords: Türk dış politikası; Enerji arz güvenliği; Doğu Akdeniz doğal gazı; Enerji merkez ülke; Doğal gez geçiş ülkesi; Doğu Akdeniz doğal gaz boru hattı; Turkish foreign policy; Energy supply security; Eastern Mediterranean natural gas; Energy hub country; Natural gas transit hub country; EastMed pipeline